Una picciola favoletta. La fortuna della metafora vichiana nel Novecento - Emma NANETTI (Laboratorio dell'ISPF, 2018)
[Una picciola favoletta. The fortune of Vico’s metaphor in the Twentieth Century]. Vico’s idea of metaphor, as it emerges by reading the main works of the Neapolitan philosopher, is still alive more than ever, and it invites us to reconsider our cognitive modalities that, in obedience to the Cartesian cult of logic and objectivity, often operate in detriment to fantasy and emotions.